Encyclopedia of e-commerce, e-government, and mobile commerce - Khosrow-Pour, Mehdi, 1951-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
This two volume encyclopedia covers the e-technologies field. It includes contributions highlighting current concepts, trends, challenges, applications, and dot.com experiences in the field of e-commerce, e-government, and mobile commerce. With over 200 contributions from more than 300 experts and researchers worldwide, and extensive reference sections which list 4,400 additional research works, this encyclopedia stands as a comprehensive, research-based encyclopedia in the ever-evolving field of e-commerce, e-government and mobile commerce.
v. 1. A - J -- v. 2. K - Z.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 31, 2010).
Keywords: Electronic commerce -- Encyclopedias; Internet in public administration -- Encyclopedias; Mobile commerce -- Encyclopedias; E-collaboration; E-commerce advertising; E-commerce agents; E-commerce applications & technologies; E-government applications & technologies; E-healthcare technologies; E-healthcare security & privacy; E-marketplaces; B2B e-commerce; Cyber public relations; Cyber identity theft; Digital rights management; Dot-com businesses; E-adoption in SMEs; Electronic voting; End user security; Mobile advertising; Mobile agents; Mobile banking and payments; Mobile commerce applications and technologies; Online security and privacy; Personal privacy in e-services; Trust in e-commerce; Virtual communities; Virtual enterprises; Web-based learning; Web portals; Web services; Wireless systems; Electronic books